Maprotiline Suppresses Cholesterol Biosynthesis and Hepatocellular Carcinoma Progression Through Direct Targeting of CRABP1 - Zheng, Cancan; Zhu, Yidong; Liu, Qinwen; Luo, Tingting; Xu, Wenwen (Frontiers in Pharmacology, 2021)
Hepatocellular carcinoma (HCC) remains one of the leading causes of cancer-related death and has a poor prognosis worldwide; thus, more effective drugs are urgently needed. In this article, a small molecule drug library composed of 1056 approved medicines from the FDA was used to screen for anticancer drugs. The tetracyclic compound maprotiline (maprotiline), a highly selective noradrenergic reuptake blocker, has strong antidepressant efficacy. However, the anticancer effect of maprotiline remains unclear. Here, we investigated the anticancer potential of maprotiline in the HCC cell lines Huh7 and HepG2. We found that maprotiline not only significantly restrained cell proliferation, colony formation and invasion in vitro but also exerted antitumor effects in vivo. In addition to the antitumor effect alone, maprotiline could also enhance the sensitivity of HCC cells to sorafenib. In depth studies revealed that maprotiline substantially decreased the phosphorylation of sterol regulatory element-binding protein 2 (SREBP2) through the ERK signaling pathway, which resulted in decreased cholesterol biosynthesis and eventually impeded HCC cell growth. Furthermore, we identified cellular retinoic acid binding protein 1 (CRABP1) as a direct target of maprotiline. In conclusion, our study provided the first evidence showing that maprotiline could attenuate cholesterol biosynthesis to inhibit the proliferation and metastasis of HCC cells through the ERK-SREBP2 signaling pathway by directly binding to CRABP1, which supports the strategy of repurposing maprotiline in the treatment of HCC.